Study on the absence of legal regulations in the acquisition of SOAT (Compulsory Insurance for Traffic Accidents) in foreign citizens in the Tacna region. - Sarmiento Chambi, Herminia (2014)
Objective: Determine the impact of regulations on the compulsory acquisition of SOAT by foreigners in the protection and safety of victims of traffic accidents. Method: The research is relational, relational descriptive nature, because it is based on measuring the properties of the study variables: SOAT regulations acquisition by foreigners; and safety and security of victims of traffic accidents. Design (not experimental) relational description was adopted as the independent variable is not manipulated; is perceived and measured the direct relationship between two or more concepts or variables. Result: Were analyzed and interpreted the information processed through quantitative, qualitative analysis, and synthesis, determining the impact of the regulations on compulsory acquisition of SOAT by foreigners in the protection and safety of victims of traffic accidents. Conclusions: In the Tacna Region, the protection and safety of victims of traffic accidents is poor. In the Tacna Region, the implementation of regulations SOAT acquisition by foreigners is inadequate, after finding that the regulation of the standard application mode, the observed guarantee impunity; and the high percentage of traffic accidents observed in the period 2011 -2012 by foreigners do not allow efficient implementation.